Detrimental and essential elements in fruiting bodies of mushrooms with ecological relationship to birch (Betula sp.) collected in the Bohemian Forest, the Czech Republic - Krejsa, Jiří; Šíma, Jan; Kobera, Marek; Šeda, Martin; Svoboda, Lubomír (Environmental science and pollution research international, 2021)
Four macrofungi species with ecological relationship to birch (Betula sp.) were analyzed with regard to the content of 21 detrimental and essential elements in their fruiting bodies. Two of the species (Leccinum scabrum and Leccinum versipelle) were mycorrhizal forming edible fruiting bodies while the others (Fomitopsis betulina and Inonotus obliquus) parasitic used in alternative medicine. The samples were collected near the town of Vimperk in the Bohemian Forest, the Czech Republic. L. scabrum accumulated Ag, Rb, Cd, Cs, Se, Cu, and Zn with bioconcentration factors of 22, 5.5, 4.7, 3.2, 2.0, 1.7, and 1.4, respectively. Similar trend in bioconcentration was revealed for L. versipelle with bioconcentration factors of 28, 5.2, 2.4, 1.9, 1.6, and 1.6 determined for Ag, Rb, Cu, Se, Zn, and Cd, respectively. Considerably high contents of Ca (400 ± 190 mg kg-1 dry matter), Fe (110 ± 30), Mg (1100 ± 300), and Zn (220 ± 90) were found in F. betulina. Similarly, high contents of Ca (1000 ± 700 mg kg-1 dry matter), Fe (110 ± 30), Mg (2000 ± 1100), Mn (410 ± 270), Rb (160 ± 60), and Zn (140 ± 70) were determined for I. obliquus. The different lifestyles (mycorrhizal vs. parasitic) were reflected in 13 significant differences of element contents.
Keywords: Environmental pollution; Polsko; Bioconcentration of elements; Betula sp.; Betula; Trace elements; Fruiting Bodies, Fungal; plodnice hub; stopové prvky; bříza; Czech Republic; Česká republika; Forests; Alternative medicine; Wild growing edible mushrooms; Trace Elements; lesy; Poland; Agaricales